PENGARUH PENDIDIKAN KESEHATAN IMUNISASI DPT TERHADAP SIKAP IBU DALAM PEMBERIAN IMUNISASI DI DESA KALIDILEM KECAMATAN RANDUAGUNG KABUPATEN LUMAJANG - Hidayati, Nurul; Ekasari, Tutik; Zakiyyah, Muthmainnah (NHM PRESS, 2023)
The lack of completeness of immunization will have an impact on health and vulnerability to seven main diseases. The aim of the study was to analyze the influence of DPT immunization health education on mothers' attitudes in administering immunizations in Kalidilem Randuagung Lumajang. This research was a quantitative research by design quasi experiment. The population of all mothers who have babies aged 2-6 months in Kalidilem Randuagung Lumajang is 30 people. Respondents are taken by technique total sampling, using Wilcoxon Test. The results of the study showed that the majority of mothers in Kalidilem Randuagung Lumajang had a negative attitude toward giving immunization before being given DPT Immunization Health Education as many as 21 respondents (70%) had a positive attitude as many as 19 respondents (63.3%). The Wilcoxon test results show a value of α <0.05, namely (0.000) that there is The Effect of DPT Immunization Health Education on Mother's Attitudes in Giving Immunizations in Kalidilem Randuagung Lumajang. Efforts to increase immunization coverage according to the target are by increasing mother's knowledge about immunization. Increase mothers’ knowledge by providing appropriate health education.